Laboratory exercises in microbiology - Harlay, John P. (McGraw-Hill education, 2005)
Laboratory Exercises in Microbiology, 6/e has been prepared to accompany Prescott et al's "Microbiology, 6/e". Like the text, the laboratory manual provides a balanced introduction to laboratory techniques and principles that are important in each area of microbiology